Insecticide Usage in Lotus-Fish Farming and Its Impact on Fish Culture and Grower Health - S. Bumroongsook (My University, 2018)
Insect pest is a major problem of lotus flower production for local markets and export. Lotus growers inappropriately use high quantity of toxic insecticides to control insect pest. Insecticides are applied all over the lotus farming and the chemical substances are not limited to lotus flowers but they leach down to the water reservoir affects fish and other nontarget living organisms in water and the environment. Therefore, the survey of insecticides usage and related information for lotus-fish farming in 3 different provinces: Chachoengsao, Suphanburi and Nakhonpathom was conducted. The result showed most growers had an elementary school certificate while the rest held a secondary school certificate. The important insect pest of lotus are thrips (Frankliniella schultzei) and common cutworm (Spodoptera litura). Lotus growers preferred organophosphate insecticides the most, followed by the avermectin group. Most growers from Chachoengsao(89.9%), Nakhonpathom(84.1%) and Suphanburi(77.4%) had insecticide application regularly. Decontamination of insecticidal residue on lotus flowers after harvest could be done by using flower dipping in water before distribution. Concerning over fish culture in lotus-fish farming, growers used the insecticide that had least effect on fish. However, the chemical application might cause the slow growth of fish. None of fish kill occurred due to insecticide application for insect control in lotus-fish farming. Repeated exposure to insecticide during application causes health problems to the growers.
Keywords: Aquatic Ecosystems and Phytoplankton Dynamics